Extent of parental involvement in the education of children with down syndrome - Anteola, Thelma B. (Animo Repository, 2011)
This study has for its general purpose, the determination of the extent of parental involvement in the education of their children with Down Syndrome. Analysis were made through statistical treatment applying the frequency count, percentage, rank order, weighted mean and t-test. Generally, parents are highly involved in the education of their child with Down Syndrome. Thus, the knowledge, skill and ability level of parents in educating their child with Down syndrome is greatly affected by several variables such as age, gender, educational attainment, occupational status and number of years the child has been in SPED school.